THE POTENTIAL IMPACT OF THE AFRICAN CONTINENTAL FREE TRADE AREA (AFCFTA) ON MULTINATIONAL COMPANIES IN SOUTH AFRICA - Aleck M Mokoena, Sheilla Nyasha (USV Annals of Economics and Public Administration, 2024)
The world is currently going through the intensified stage of globalisation and socio-economic interdependence characterised by different policies, processes, rules, propositions and regulations. In Africa, in 2018, the African Free Trade Area (AfCTA) was established encompassing most of Africa. The purpose of this study was to assess the potential impact of the African Continental Free Trade Agreement (AfCFTA) on South African multinational corporations (MNCs). The study examined the theories of Functionalism and Transactionalism to highlight country interdependence and how the terms of free trade agreements, such as those provided by the AfCFTA, may help nations harness AfCFTA advantages for mutual gain. An examination of multinational companies' operations in the context of trade based on the AfCFTA revealed that South African MNCs gain from such an agreement in both the short and long run. This conclusion was reached using primary data gathered from purposively sampled individuals knowledgeable about the MNCs in the Gauteng Province, policymakers, and a trade research think tank. Based on the sample size of 12, gathered data was analysed qualitatively using thematic analysis approach. It was further discovered that, while MNCs operating within the scope of the AfCFTA may potentially experience some short-term and long-term benefits, they may also face some challenges, such as exposure to intense local competition, intellectual property theft through product imitations, and poor infrastructure. As a result, it was proposed that some structural changes be made to the AfCFTA and that infrastructure investment be raised in order to boost the performance of MNCs in South Africa and enhance their benefit from the AfCFTA.